1973
DOI: 10.1021/ja00788a005
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of silane hydride anion (SiH5-) and model studies of inter- and intramolecular exchange in pentacoordinate silicon species. Ab initio investigation

Abstract: behavior. However, (F) almost has a monotonic behavior, the calculated value for NF2 being 0.003 au too small. The same problem occurs for , with only the calculated NF2 value preventing a monotonic increase across the series.In summary, then, most of the theoretical properties follow one of two patterns: (a) a monotonic increase or decrease across the series or (b) a potential curve-like behavior with maximum or minimum at CF2. The simplest understanding of these two patterns may be in the fact that the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The electron withdrawing nature of the chloro-substituents in HSiCl 3 enhances the electrophilicity of the silicon atom, which promotes hypervalency and also enhances the reactivity of the Si−Cl bonds. 3234 In the second step, a chloride anion cleaves off from the silicon atom and forms a hydrogen bond with the 4-OH group (as indicated by O in Figure 2) of the O -or N -methylglucuronide, concerted with formation of a Si−O bond. Elimination of an HCl molecule yields the ionic product [M − H + HSiCl 3 − HCl] − (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron withdrawing nature of the chloro-substituents in HSiCl 3 enhances the electrophilicity of the silicon atom, which promotes hypervalency and also enhances the reactivity of the Si−Cl bonds. 3234 In the second step, a chloride anion cleaves off from the silicon atom and forms a hydrogen bond with the 4-OH group (as indicated by O in Figure 2) of the O -or N -methylglucuronide, concerted with formation of a Si−O bond. Elimination of an HCl molecule yields the ionic product [M − H + HSiCl 3 − HCl] − (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the calculations, the reactions are initiated by binding of HSiCl 3 to the carboxylate group of the deprotonated glucuronic acid, generating a covalently bound pentacoordinated silicon anion that is in close proximity to the 4-OH group (Figure ). The electron withdrawing nature of the chloro-substituents in HSiCl 3 enhances the electrophilicity of the silicon atom, which promotes hypervalency and also enhances the reactivity of the Si–Cl bonds. In the second step, a chloride anion cleaves off from the silicon atom and forms a hydrogen bond with the 4-OH group (as indicated by O in Figure ) of the O - or N -methylglucuronide, concerted with formation of a Si–O bond. Elimination of an HCl molecule yields the ionic product [M – H + HSiCl 3 – HCl] − (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…It has long been known that the electronic structures of the isoelectronic CH 5 – and SiH 5 – anions are remarkably different. The carbon anion is a transition state, [CH 5 – ] ‡ , for the H – + CH 4 → CH 4 + H – exchange reaction and lies nearly 50 kcal/mol above the reactants and products. The silicon anion, SiH 5 – , is a stable molecule that is bound by more than 20 kcal/mol relative to SiH 4 + H – .…”
Section: Discussionmentioning
confidence: 99%
“…− and SiH 5 − molecules are isoelectronic, the early calculations of Wilhite and Spialter, 1 Baybutt, 2 and Keil and Ahlrichs 3 indicated that these anions are very different species. CH 5 − is the high-energy saddle point for the S N 2 exchange reaction…”
Section: Introduction Although the Chmentioning
confidence: 99%
“…Data of ab initio calculations of the reaction of the SiHs formation, when silane is attacked by a hydride ion [43][44][45], and of the serniempirical MNDO calculation of the SN2 reaction pathway (R3SiX + X-; X = halide, R = HI Alkyl) (46) pre~ict a backside approach for the electronegative nucleophilic groups Y with respect to the group X being substituted. The preferability of the trigonal-bipyramidal bond configuration of the pentacoordinate silicon atom XIXa is also predicted.…”
Section: Intramolecular Tautomeric System Design 183mentioning
confidence: 99%